2007
DOI: 10.1063/1.2714666
|View full text |Cite
|
Sign up to set email alerts
|

Partial magnetization reversal in a perpendicular exchange-biased [Pd∕Co]∕FeMn film through laser annealing

Abstract: Partial magnetization reversal on the perpendicular exchange-bias characteristics in the [Pd∕Co]×5∕FeMn bilayered and [Pd∕Co]×2∕Cu∕Co∕[Pd∕Co]×2∕FeMn spin valve thin films was investigated using laser. The hysteresis loops were measured using the extraordinary Hall effect and magneto-optical Kerr effect (MOKE). By increasing the output intensity of the laser, the exchange-bias fields in the [Pd∕Co]×5∕FeMn bilayered thin film were gradually changed from negative to positive. The distribution of partial magnetiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A survey of most of EB experiments on the magnetic field applied during field cooling from above the blocking temperature and thermal decay of EB under a magnetic field antiparallel to the pinning direction reveals that the heat treatment time is almost several tens of minutes [23][24][25]. In addition, laser annealing experiments on NiFe/FeMn films demonstrated that the energy required to reverse the EB was approximately 90-360 J [26,27]. However, the energy generated by the current pulse in our experiment was approximately 0.85-0.21 J, which is much lower than the energy required.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A survey of most of EB experiments on the magnetic field applied during field cooling from above the blocking temperature and thermal decay of EB under a magnetic field antiparallel to the pinning direction reveals that the heat treatment time is almost several tens of minutes [23][24][25]. In addition, laser annealing experiments on NiFe/FeMn films demonstrated that the energy required to reverse the EB was approximately 90-360 J [26,27]. However, the energy generated by the current pulse in our experiment was approximately 0.85-0.21 J, which is much lower than the energy required.…”
Section: Introductionmentioning
confidence: 98%
“…To date, many other post-deposition strategies have been used for EB tuning, such as electric field control [32][33][34], magnetic field control [35][36][37], ion irradiation [38,39], and laser annealing [26,27]. However, many of these approaches have disadvantages.…”
Section: Introductionmentioning
confidence: 99%